Updates in Pediatric Sleep and Child Psychiatry - Ivanenko, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Sleep-related symptoms are common in the majority of psychiatric diagnostic categories. The overlap of sleep and psychiatric disorders have been demonstrated in numerous studies. The understanding of sleep and child psychiatry has progressively evolved in the last decade and newer insights have developed regarding the complex interaction between sleep and psychopathology. This collection of articles represents updates on sleep and psychiatric disorders with medical and neurological co-morbidities in children and adolescents.